Dampak Trade War Amerika Serikat VS China Terhadap Saham Syariah di Bursa Efek Indonesia - Hadi, Nor; Malikhah, Aminatul; Alfie, Atieq Amjadallah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This study aims to determine the impact of the United States VS China trade war events on the performance of islamic stocks on shares incorporated in the index JII 2018 period by looking at the market reaction using 3 measurement proxies namely abnormal returns, trading volume activity and bid-ask spread . This research uses a quantitative approach with secondary data taken from www.idx.co.id. The population in this study is all shares included in the JII index. Data collection techniques in the study used documentation. While the data analysis technique uses the Wilcoxon signed rank test. The results of this study indicate that (1) there is no significant difference in average abnormal return (AAR) before and after trade war on the JII index; (2) there is a significant difference in average trading volume activity (ATVA) before and after the trade war on the JII index; (3) there is no significant difference in bid-ask spread (BAS) before and after the trade war on the JII index.